UIN Mahmud Yunus Batusangkar’s Public Relations Strategy for Branding the Islamic Science Campus: A Reflection of the Minangkabau Surau on TikTok - WulanTrimay Arta Arta; Refika Mastanora (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study examines the public relations strategy in building the image of UIN Mahmud Yunus Batusangkar through the social media platform TikTok. Social media is considered an essential element in branding strategies as it provides various features that support the process, enabling higher education institutions to optimize their branding efforts.The main focus of this research is on the branding strategies implemented by the university’s public relations department, which are divided into three aspects: Brand Positioning, Brand Identity, and Brand Personality. The research employed a descriptive qualitative method, with data collection techniques including interviews, observations, and documentation. The collected data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. To ensure data validity, source triangulation was conducted. The purpose of this research is to identify the strategies used by the public relations team in branding the university. The findings reveal that: 1) Brand Positioning Strategy. Developing TikTok content aligned with digital media developments and showcasing the uniqueness of UIN Mahmud Yunus Batusangkar as an Islamic Science Campus Reflecting the Minangkabau Surau, positioning the campus as a center for Islamic studies. 2). Brand Identity Strategy. Optimizing TikTok features that support the branding process and maintaining consistency in presenting informative content with attractive designs that reflect the identity of the Islamic Science Campus Reflecting the Minangkabau Surau. 3) Brand Personality Strategy. Carrying out a brand-building process through social media regularly and consistently, highlighting all relevant information about UIN Mahmud Yunus Batusangkar, and enhancing prospective students’ perceptions. This research underscores the importance of utilizing social media, particularly TikTok, in higher education branding strategies. Through a structured and consistent approach, the university’s public relations team can build a strong and appealing image for their target audience.